Life insurance cash flows with policyholder behavior - Kristian Buchardt; Thomas Møller (Risks, 2015)
The problem of the valuation of life insurance payments with policyholder behavior is studied. First, a simple survival model is considered, and it is shown how cash flows without policyholder behavior can be modified to include surrender and free policy behavior by calculation of simple integrals. In the second part, a more general disability model with recovery is studied. Here, cash flows are determined by solving a modified Kolmogorov forward differential equation. We conclude the paper with numerical examples illustrating the methods proposed and the impact of policyholder behavior.
Keywords: 330; Kolmogorov's differential equations; surrender; free policy; Solvency 2